A Nontoxic Bifunctional (Anti)Solvent as Digestive‐Ripening Agent for High‐Performance Perovskite Solar Cells. Issue 14 (21st February 2020) - Yun, Yikai; Wang, Fangfang; Huang, Hongyan; Fang, Yinyu; Liu, Sizhou; Huang, Wenchao; Cheng, Zhengchun; Liu, You; Cao, Yezhou; Gao, Mei; Zhu, Lin; Wang, Lin; et al.
Abstract: The preparation of high‐quality perovskite films is important for achieving high‐performance perovskite solar cells (PSCs). The effective balance between solvent and antisolvent is an essential factor for regulating high‐quality perovskite film during the spin‐coating and thermal‐annealing steps. In this work, a greener, nonhalogenated, nontoxic bifunctional (anti)solvent, methyl benzoate (MB), is developed not only as an antisolvent to rapidly generate crystal seeds at the perovskite spin‐coating step, but also as a digestive‐ripening solvent for the perovskite precursors, which can prevent the loss of organic components during the thermal‐annealing stage and effectively suppress the formation of miscellaneous lead halide phases. As a result, this novel bifunctional (anti)solvent is employed in planar n–i–p PSCs for engineering high‐quality perovskite layers and thus achieving a power conversion efficiency up to 22.37% with negligible hysteresis and >1300 h stability. Moreover, due to the high boiling point and low‐volatility characteristic of MB, high‐performance PSCs are achieved reproducibly at different operating temperatures (22–34 °C). Therefore, this developed bifunctional solvent system can provide a promising platform toward globally upscaling and commercializing PSCs in all seasons and regions. Abstract : A novel bifunctional (anti)solvent system is developed for regulating the perovskite crystallization procedure. It can perform not only as an antisolvent at the spin‐coating step to rapidly generate crystal seeds, but also as a solvent for ripening the precursors to large crystal grains during the thermal‐annealing process. Therefore, it can significantly enhance the efficiency, stability, and reproducibility of perovskite solar cells.